A 3-Years Pneumonia Incidence in Burn Cases with Inhalation Injury at the Burn Center of Dr. Soetomo General Hospital Surabaya in 2015-2018 - Salsabilla Gina Rania; Lynda Hariani; Helmia Hasan; Iswinarno Doso Saputro (JUXTA: Jurnal Ilmiah Mahasiswa Kedokteran Universitas Airlangga, 2022)
Introduction: Inhalation injury is one of burns impact. Airway burns due to inhalation injury is a non-specific term which refer to all respiratory tract injuries occurred due to irritative chemicals, including heat and smoke during inspiration. Inhalation injury increases the risk of death in burns. Pneumonia is one of burns-related inhalation injury complications.Methods: This was a descriptive retrospective study aiming to determine the incidence of pneumonia in burn patients with inhalation injury using secondary data at Burn Center Dr. Soetomo General Hospital Surabaya in the period of January 2015 - December 2018.Results: There were 5 cases of pneumonia in 14 burn cases with inhalation injury (35.71%). Respectively, 2 and 3 cases were found in 2017 and 2018. There were 2 female (40%) and 3 male (60%) patients, with age varied within 28-73 years old. The burn area of burn patients with inhalation injury and pneumonia were found by 15%, 20%, 24%, 32% and 71%, or within the classification of 11-20% burn area, and most complication found was hypoalbuminemia, as much as 3 cases (60%).\Conclusion: Most pneumonia in burn cases with inhalation injury was occurred in 2018, dominated by male patients. The age of the patient were ranging from early adulthood to elderly. Most burns were in the range of 11-20% burn area with the most complication found was hypoalbuminemia.